Copper catalyzed photoredox synthesis of α-keto esters, quinoxaline, and naphthoquinone: controlled oxidation of terminal alkynes to glyoxals - Das, Deb Kumar (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Herein, we report a facile visible light induced copper catalyzed controlled oxidation of terminal C[triple bond, length as m-dash]C alkynes to α-keto esters and quinoxalines via formation of phenylglyoxals as stable intermediates, under mild conditions by using molecular O(2) as a sustainable oxidant. The current copper catalysed photoredox method is simple, highly functional group compatible with a broad range of electron rich and electron poor aromatic alkynes as well as aliphatic alcohols (1°, 2° and 3° alcohols), providing an efficient route for the preparation of α-keto esters (43 examples), quinoxaline and naphthoquinone with higher yields than those in the literature reported thermal processes. Furthermore, the synthetic utility of the products has been demonstrated in the synthesis of two biologically active molecules, an E. coli DHPS inhibitor and CFTR activator, using the current photoredox process. In addition, we applied this methodology to the one-pot synthesis of a heterocyclic compound (quinoxaline, an FLT3 inhibitor) by trapping the intermediate phenylglyoxal with O-phenylenediamine. The intermediate phenylglyoxal can also be isolated and further reacted with an internal alkyne to form naphthoquinone. This process can be readily scaled up to the gram scale.